Noi cercetări arheologice la cetatea Saschiz I. Incinta exterioară - Marcu Istrate, D.; Dobrotă, S.; Rezi, B.; Gál, S. (Materiale și Cercetări Arheologice)
Saschiz, once one of the most important Saxon settlements of eastern Transylvania, located 23 km away from Sighisoara, was included decades ago in the UNESCO world heritage list. On a rocky hill north‑west of the village rises its refuge fortress, whose beginnings have been archaeologically ascribed to the early 15th century based on the research undertaken in 1999–2000, the first investigation of this kind undertaken on site. In 2018, the fortress entered restoration, and in 2023 a large‑scale archaeology research project was initiated, involving excavations both inside the area of the preserved fortified structure – formerly the main ward of the fortress – and beyond it, in the area where the outer ward once stood. Due to the amount of data and materials collected during the 2023 investigation, the research results will be published gradually, as they are being processed. This paper, the first one in the series, concerns the findings from the area of the outer ward, of which at the start of the research only the ruins of the two towers that were flanking the southern entrance could still be clearly discerned. The investigation established the planimetry of the southern and eastern defensive walls of the outer ward, identified the ruins of a smaller eastern tower midway on the eastern rampart and discovered that the course of the fortifications extended much in the north‑east, to encompass a small terrace. All newly identified wall structures were in poor condition, a situation that may be partially explained through the miserly use of mortar and the common employment of dry foundations. The material finds were scarce, and most of them seemed to be castoffs from the main ward rather than actual signs of activity in the outer ward. The discovery of a grave, likely medieval or post‑medieval, overlapped by the foundations of the southern gate tower, contributed little to dating the construction of this outer fortification. While it has been long established that the rampart of the outer ward was attached to the School Tower of the main ward, the time of its construction remains doubtful, although the uneven and meagre construction techniques employed may plead for a late period, when the community of Saschiz had already went into decline.